Sāyaṇa's Upodghāta to the Taittirīya Saṁhitā and the Ṛgveda Saṁhitā - Sāyaṇa 1320-1387 (Pratibha Prakashan, 1999)
Study of the Sāyaṇa's introductions of the Taittiriyasaṃhitā and R̥gveda.
Text in Devanagari-Schr., Sanskrit und engl.- Einl. in engl. Sprache
Keywords: Vedas. -- Yajurveda. -- Kr̥ṣṇayajurveda (Taittirīyasaṃhitā) -- Introductions; Vedas. -- R̥gveda -- Introductions